Modeling of Mutual Inductance Between Two Misalignment Planar Coils in Wireless Power Transfer - Qian, Libo; Chen, Mengfei; Cui, Kexue; Shi, Ge; Wang, Jian; Xia, Yinshui (IEEE microwave and wireless components letters, 2020)
Mutual inductance is an important parameter for the design and optimization of the wireless power transfer (WPT) system. In this letter, a compact analytical model for mutual inductance of two coupled planar coil is proposed. The model is derived from Neumann's integral of constant current-carrying filament with a Taylor expansion approach. It can predict mutual inductance at various lateral and angular misalignments. The analytical results show a good agreement with the 3-D electromagnetic simulation results, and the maximum error for the mutual inductance remains less than 15.1%. An experimental setup has been built, and the results reveal the proposed model can predict the mutual coupling rapidly and effectively.